2018
DOI: 10.7717/peerj.5426
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of pollination by frugivorous birds in Neotropical Myrtaceae

Abstract: Bird pollination is relatively common in the tropics, and especially in the Americas. In the predominantly Neotropical tribe Myrteae (Myrtaceae), species of two genera, Acca and Myrrhinium, offer fleshy, sugary petals to the consumption of birds that otherwise eat fruits, thus pollinating the plants in an unusual plant-animal interaction. The phylogenetic position of these genera has been problematic, and therefore, so was the understanding of the evolution of this interaction. Here we include new sequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…2). Several previously documented cases of bird pollination of nectarless flowers also reported that floral tissues were consumed (Sérsic & Cocucci 1996, Dellinger et al 2014, Nadra et al 2018. We are unable to comment on the relative nutritional value of the floral components and/ or parasitising gall insects, but it is known that two other species of parrot occurring in our study region (Swift Parrot Lathamus discolor and Musk Lorikeet Glossopsitta concinna) intentionally consume and digest the pollen of Eucalyptus (Gartrell & Jones 2001, Hingston et al 2004a.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…2). Several previously documented cases of bird pollination of nectarless flowers also reported that floral tissues were consumed (Sérsic & Cocucci 1996, Dellinger et al 2014, Nadra et al 2018. We are unable to comment on the relative nutritional value of the floral components and/ or parasitising gall insects, but it is known that two other species of parrot occurring in our study region (Swift Parrot Lathamus discolor and Musk Lorikeet Glossopsitta concinna) intentionally consume and digest the pollen of Eucalyptus (Gartrell & Jones 2001, Hingston et al 2004a.…”
Section: Discussionmentioning
confidence: 77%
“…A. dealbata is the earliest flowering of all Tasmanian acacias and if outcrossing by insects was of critical evolutionary importance then we might expect that selection pressure on the phenology would have caused a shift to later flowering. The species does not produce nectar from either flowers or extra-floral nectaries and this, together with the yellow flowers and distinctive scent, is inconsistent with traditional bird pollination syndromes which are characterised by the production of abundant nectar to support energetic needs, red colour, and little scent (Faegri & van der Pijl 1979, Nadra et al 2018. However, since some bird species were observed to consistently feed on and among the flowers (table 3) they must clearly be deriving some benefit.…”
Section: Discussionmentioning
confidence: 90%
“…The geographic distribution of the complex extends from Mexico to northern Argentina and Uruguay, including the Antilles ( Figure 4 ). A molecular phylogenetic analysis shows P. guajava and P. guineense as sister taxa ( Salywon, 2003 ), but the relationships with the other species are unclear due to lack of representation ( Rivero et al, 2012 ; Nadra et al, 2018 ).…”
Section: Natural History Of Psidium Guajavamentioning
confidence: 99%
“…Phylogenetic studies based on nuclear and plastid DNA regions have confirmed the monophyly of Psidium with Myrrhinium as its sister group (Lucas et al, 2005;Vasconcelos et al, 2017;Nadra et al, 2018;Flickinger et al, 2020). However, evolutionary relationships within the genus remain unresolved due to its high rates of diversification (Vasconcelos et al, 2017), its wide Neotropical distribution (Richardson and Rejmánek, 2011;Landrum, 2017), variable ploidy levels (Costa and Forni-Martins, 2007), and hybridization among species (Landrum et al, 1995).…”
Section: Systematics and Taxonomy Of Guavamentioning
confidence: 99%